Dictionary of physical metallurgy in five languages : English, German, French, Russian, and Spanish - Freiwillig, Rudolf (Elsevier, 1987)
This dictionary reflects developments in physical metallurgy, namely the growth of strong ties to the physics of metals. Thus the terms relating to lattice defects and their properties and to laboratory tests revealing their effects on macroscopic behaviour of metallic materials, are extensively covered. Theory of dislocations and work hardening, high temperature deformation, fatigue and fracture, metallography and phase changes are all broadly covered, whilst terms related to technical operations such as heat and mechanical treatment as well as the corresponding equipment have been incorporated to a lesser extent. The work is based on the Dictionary of Scientific Terms from Physical Metallurgy published in parts during the years 1968-1976 in the Czechoslovak journal Metallic Materials and on its revised and extended version published in 1981 by Veda, the publishing house of the Slovak Academy of Sciences. The Czech and Slovak languages of the two preceding versions have been omitted, and Spanish has been included; the Russian part has been substantially complemented by synonyms. The dictionary provides university students, research workers and engineers with the vocabulary of basic terms used in this branch of science. It is also a useful tool for translators.